Prevalence and Determinants of Compulsive Buying: A Systematic Review with Preventive Implications - Sol-Gámez, Judith; Molinari-Conde, Guadalupe; Vázquez-Martínez, Andrea; Villanueva-Blasco, Víctor José (Acciones e Investigaciones Sociales, 2025)
Introduction: Numerous studies examine the variables of compulsive buying (CB), but there is no systematic review unifying them. The aim of this study is to analyse the international prevalence rates of CB, establish a risk profile and examine its risk and protective factors to enable preventive intervention. Material and Methods: A systematic literature review was conducted using PubMed, Cochrane, Web of Science, ProQuest, and Scopus, covering the last 11 years and following PRISMA methodology. The search was performed between November 2023 and May 2024. A total of 52 international studies were reviewed, with an average methodological quality of 85.38% according to MMAT criteria. The main biases found in the studies were selection bias and non-response bias. Results: Results indicate that 74% of individuals with compulsive buying behaviour were women aged 18 to 30 years, and various variables can predict this issue. CB is associated with substance addiction, workaholism, and problematic use of the internet and social media. Discussion: In order to standardise prevalence rates internationally, a validated and unified measurement tool must be developed. Further research is needed to investigate environmental risk factors as well as the relationship between CB and other addictions. It is essential to recognize this disorder with the diagnostic importance it deserves to facilitate preventive measures. Theoretical and practical implications of the findings are discussed in terms of designing preventive programs.